Development of an Ethnomathematics-Based Worksheet Integrating the Traditional Engklek Game to Enhance Elementary Students’ Spatial Ability on Cuboid Nets - Khalia, Shindy; Mufliva, Rosiana; Pradani, Qiyamullaila Putri; Septia, Eka; Fawwazelita, Nadiya; Damayanti, Denissa Sri; Erinda, Dwi (International Conference on Elementary Education, 2025)
This study was motivated by the fact that mathematics learning in elementary schools is still largely procedural and memorization-oriented, causing students to struggle in understanding spatial concepts, particularly in the topic of cuboid nets. Spatial ability plays an essential role in supporting reasoning and geometric visualization. Integrating cultural contexts through ethnomathematics can serve as a solution to create meaningful and contextual learning. One relevant local culture is the traditional Engklek game, which contains geometric patterns, symmetry, and spatial movements related to the concept of cuboid nets. This study aimed to develop an ethnomathematics-based student worksheet integrating the Engklek game to improve elementary students’ spatial ability. The research employed the Design and Development method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results indicated that the developed worksheet was highly feasible and effective, achieving 90.8% from material and media experts and 95.8% from teaching practitioners. The Engklek-based worksheet effectively enhanced students’ spatial visualizationskills while fostering cultural awareness and appreciation of Indonesian heritage through meaningful and contextualized mathematics learning